Exploring the factors that influence smartphone usage for learning among students at a public university in Malaysia - Mahat, Jazihan; Ibrahim, Norasyikin; Mohd Ayub, Ahmad Fauzi (Human Resource Management Academic Research Society, 2023)
Smartphones have become essential in student life, especially for educational purposes. This study examines smartphone usage for learning among students at a Malaysian public university. The research utilised correlational research design to investigate the relationships between habitual behaviour, hedonic motivation, and facilitating conditions on students’ smartphone usage for learning. Responses from 373 students were collected for this purpose using stratified random sampling. The results demonstrate a strong positive correlation between habitual behaviour and smartphone usage for learning, indicating the crucial role of habitual behaviour. The correlations between hedonic motivation and facilitating conditions with smartphone usage for learning were significant, although relatively weaker. The results of the multiple regression analysis highlighted the significant impact of habitual behaviour, which accounted for 88.1% of the observed variance, on smartphone usage for learning. The findings highlight the importance of routine behaviour on students' use of smartphones for academic purposes, offering valuable insights for educators and institutions seeking to enhance the integration of smartphones in educational environments.